MAXIM FLOUTING IN 'DAVID LETTERMAN SHOW': AN EPISODE WITH AISHWARYA RAI - Didin Nuruddin Hidayat; Vera Nurlia; Alek Alek; Yudi Septiawan (Leksema: Jurnal Bahasa dan Sastra, 2020)
This study analyzed the maxim flouting in David Letterman and Aishwarya Rai in David Letterman Show,. This study aims to find out which types of maxim flouting are performed by David Letterman as the host and Aishwarya Rai as the guest in the talkshowas well as to describe the reasons why the maxim flouting performed by the two. Qualitative research method was used in this study, and the data were presented in a descriptive analysis. This study dealt with a pragmatic approach and employed one of the Pragmatics theories, namely the Theory of Conversational Maxims or Cooperative Principle. Data in this study are analyzed pragmatically based on Grice’s Cooperative Principle and its maxims. The data of the study were the utterances of the maxim flouting performed by David and Aishwarya. They were collected by downloading the episode of the show and watching the show. The researchers used Grice’s theory called Cooperative Principles with the four types of maxims, i.e: the maxim of quality, maxim of quantity, maxim of relation, and maxim of manner to analyze the maxim flouting in the talkshow. The results showed that all four types of maxim flouting were performed by both David and Aishwarya. In conclusion, the maxim flouting happened in the talkshow were beneficial to avoid discomfort and to give more explanations.